Frequencies of Renal Pathologies in Patients with Flank Pain (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the frequencies of renal patholigies in patient with flank pain. Material and Method: All consecutive patients with flank pain reporting in urology department (Emergency and OPD) in one month, who fulfill the inclusion criteria, were advised to get an abdominal ultrasound report for their complaint. The information regarding patient along with ultrasound findings were recorded on a Performa designed with collaboration of Radiology Department. The data collected was entered in Epi Data. Statistical analysis was done by using Epi Info. The known cases of renal pathologies and other pathologies causing flank pain were excluded from the study. Results: In three month 1938 patients reported with flank pain. Among these Male patients were 774 (39.94%) while Female patients were 1164 (60.06%). 426 (21.98) patients were suffering from diseases which were renal in origin. Among these 426 patients 189 (44.37%) were Male and 237 (55.63%) were Female. The frequencies of different renal pathologies were calculated which showed renal/ureteric calculus in 258 patients (13.31% of total patient and 60.56% of patients with renal pathologies), Hydronephrosis alone in 66 patients (3.41% of total patient and 15.49% of patients with renal pathologies), Hydronephrosis along with Hydroureter in 39 patients (2.01% of total patient and 9.15% of patients with renal pathologies), Cystic renal diseases in 51 patients (2.63% of total patient and 11.97% of patients with renal pathologies),Renal tumor in 09 patients (0.46% of total patient and 2.11% of patients with renal pathologies) and Pyonephrosis in 03 patient (0.15% of total patient and 0.7% of patients with renal pathologies). Conclusion: It is not necessary that all patient presenting in hospital for flank pain have only renal pathologies. Our study concluded that other causes should also be taken under consideration. A careful history, examination and investigations can helpful in searching other causes of flank pain.
Keywords: Flank pain, Renal colic, Renal causes of flank pain, Frequency of renal pathologies, Ultrasound for flank pain